Electrochemical Biosensors for Determination of Colorectal Tumor Biomarkers (2020)
ABSTRACT: The accurate determination of specific tumor markers associated with cancer with non-invasive or minimally invasive procedures is the most promising approach to improve the long-term survival of cancer patients and fight against the high incidence and mortality of this disease. Quantification of biomarkers at different stages of the disease can lead to an appropriate and instantaneous therapeutic action. In this context, the determination of biomarkers by electrochemical biosensors is at the forefront of cancer diagnosis research because of their unique features such as their versatility, fast response, accurate quantification, and amenability for multiplexing and miniaturization. In this review, after briefly discussing the relevant aspects and current challenges in the determination of colorectal tumor markers, it will critically summarize the development of electrochemical biosensors to date to this aim, highlighting the enormous potential of these devices to be incorporated into the clinical practice. Finally, it will focus on the remaining challenges and opportunities to bring electrochemical biosensors to the point-of-care testing.